Unligated vertical vein presenting as a large atrio-portal shunt in adulthood: a case report. Issue 10 (17th October 2020) - Layton, Georgia R; Koulouroudias, Marinos; Issa, Eyad; Jepson, Steve; Corno, Antonio F; Dennison, Ashley R
Abstract: A 28-year-old male with infra-cardiac totally anomalous pulmonary venous connection (TAPVC) repaired as new-born presented in adulthood with right heart strain and very large left atrium to portal vein vessel. Residual connections from pulmonary veins to systemic circulation are believed to represent persistent 'vertical veins' (VV) not ligated at the time of the initial surgery. In our patient, since endovascular occlusion was not judged suitable, the anomalous vessel was surgically ligated and resected. A review of the literature failed to find such a procedure reported in an adult patient and analyzed the intra-operative ligation of VV during repair of TAPVC.